2019
DOI: 10.1111/jpc.14551
|View full text |Cite
|
Sign up to set email alerts
|

What evidence‐based strategies have been shown to improve breastfeeding rates in preterm infants?

Abstract: Breast milk is the preferred form of nutrition for all infants and has been shown to reduce morbidity and improve health outcomes in preterm infants. However, mothers of preterm infants face many challenges initiating and sustaining breastfeeding within the neonatal unit. This scoping review examines evidence-based practices which aim to improve breastfeeding rates in preterm infants at the time of hospital discharge. A literature review identified 17 articles which are included in this review. Supporting evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
1
12
0
12
Order By: Relevance
“…We found that participants who continued lactating over 6 weeks engaged in skin-to-skin care nearly three times longer than those who ceased lactation. These findings are consistent with previous reports of prolonged lactation when mothers of preterm infants engage in skin-to-skin care (Hilditch et al, 2019). Because skin-to-skin care may increase lactation duration, NICUs should develop evidence-based protocols and educational programs to provide nurses with guidance regarding safe and effective procedures for skin-toskin care (Kalluri et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…We found that participants who continued lactating over 6 weeks engaged in skin-to-skin care nearly three times longer than those who ceased lactation. These findings are consistent with previous reports of prolonged lactation when mothers of preterm infants engage in skin-to-skin care (Hilditch et al, 2019). Because skin-to-skin care may increase lactation duration, NICUs should develop evidence-based protocols and educational programs to provide nurses with guidance regarding safe and effective procedures for skin-toskin care (Kalluri et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Como se ha descrito en la literatura, la extracción y administración muy precoz de leche en madres de prematuros se asocia a mejor mantención de la lactancia durante la hospitalización 7,10 . No es el único factor ya que se requiere el compromiso materno para continuar con extracción cada 3 a 4 horas y transportar a la unidad de neonatología, contribuyen también el realizar contacto piel a piel diario durante la hospitalización, la colocación precoz al pecho, el uso de doble sistema de extracción y el apoyo de consejeras de lactancia para lograr un buen volumen de leche de su madre para prematuros de MBPN [11][12][13] .…”
Section: Discussionunclassified
“…Among the 36 countries in the International Neo-BFHI survey, high-income countries had the highest scores for GP 2 (Maastrup & Haiek, 2019). This could be because the introduction of familycentered care in neonatal wards, as well as the implementation of early, continuous, and prolonged skin-to-skin contact/ KMC, requires special training of medical staff, changing the model of care, and creating conditions in the wards to facilitate their implementation (Conde-Agudelo & Díaz-Rossello, 2016;Hernández-Aguilar et al, 2018;Hilditch et al, 2019;WHO & UNICEF, 2020). To successfully promote breastfeeding in maternity hospitals and children's hospitals, it is necessary to have specially trained lactation consultants, preferably IBCLCs.…”
Section: Discussionmentioning
confidence: 99%